Answer and Step-by-step explanation:
7(x-5)=x+13
Distribute the 7, then solve for x.
7x - 35 = x + 13
6x = 48 (Added 35, subtracted x)
x = 8 (Divided by 6)
One solution
-6x=-5(x-1)-x
Distribute the -5, then combine like terms. Solve for x.
-6x = -5x + 1 - x (negative times negative equals positive)
-1 = 0 (Added 6x, subtracted the x from 1x, subtracted 1)
No solution
-4(x-2)=-2(x-17/2)
Distribute the -4 and -2, then solve for x.
-4x + 8 = -2x + 17 (negative times negative equals positive) (the 2's cancel out to be 17)
-9 = 2x (Added 4x, subtracted 17)
-9/2 = x
One solution
3 - 4x + 5 = 2(8 - 2x)
Distribute the 2, combine like terms. Solve for x.
8 - 4x = 16 - 4x
0 = 8
No solution
2x + 3= +2x
3 = 0
No solution
2x+3=2x+5
0 = 2
No solution
3x+9=2.5x+14
0.5x = 5
x = 10
7(x-4)=4x+5
7x - 28 = 4x + 5
3x = 33
x = 11
One solution
5x-20=-7x-20
12x = 0
x = 0
One solution
3(2x+1)-4x=2x+3
6x + 3 - 4x = 2x + 3
2x + 3 = 2x + 3
0 = 0
Infinite solutions (The reason why this one is infinite is because if you were to plug in any value for x, the result will equal itself, like the 0 = 0.
#teamtrees #WAP (Water And Plant)